2007
DOI: 10.1016/j.ijgo.2007.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening emergency obstetric care in Nepal: The Women's Right to Life and Health Project (WRLHP)

Abstract: While the use of maternity services is still low in Nepal, improving availability and quality of EmOC together with community empowerment can increase utilization by women with complications, even in low-resource settings. Partnerships with government and donors were key to the project's success. Similar efforts should be replicated throughout Nepal to expand the availability of essential life-saving services for pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 4 publications
2
28
0
1
Order By: Relevance
“…Youngleson et al [35] attribute much of their success to the ability of administration to implement changes in policies and resource allocation within a short time frame. The AMDD project in Nepal [59] noted that the national policy allowing delegation of key obstetric first aid procedures to nurses was essential to the program impact. Two other studies [34,63] emphasise the critical role that formal support from state and district health officers played in ensuring long term commitment and support for the quality improvement initiatives.…”
Section: Resultsmentioning
confidence: 99%
“…Youngleson et al [35] attribute much of their success to the ability of administration to implement changes in policies and resource allocation within a short time frame. The AMDD project in Nepal [59] noted that the national policy allowing delegation of key obstetric first aid procedures to nurses was essential to the program impact. Two other studies [34,63] emphasise the critical role that formal support from state and district health officers played in ensuring long term commitment and support for the quality improvement initiatives.…”
Section: Resultsmentioning
confidence: 99%
“…Others have found that increasing emergency obstetric services leads to increased institutional birth and that women consider service availability when deciding where to deliver [18–20]. Importantly, a recent quasi-experimental study comparing demand- and supply-side interventions demonstrated that when financial incentive programs were followed by increased access to BEmOC, communities saw the greatest gains in institutional birth, particularly for the most impoverished groups [21].…”
Section: Introductionmentioning
confidence: 99%
“…6 This highly complex, system-level issue must be addressed across the system rather than in isolation from it. [7][8][9][10][11][12] By coordinating actions across different parts of the health system, programmes to improve maternal and neonatal health can increase coverage and reduce barriers to the use of various services. Effective programmes assemble packages of appropriate reforms in each of the six main building blocks of the health system: 1,3 governance of the health sector (to provide sectoral policy and regulatory mechanisms, and partnerships with the private sector); infrastructure and technologies (to provide emergency referral centres linked to primary care providers); human resources (to scale up the availability of skilled attendance); financing (to reduce financial barriers for patients and incentivize providers), and services (to ensure quality and an appropriate configuration of maternal and neonatal health services across all levels of care, including family planning).…”
Section: Introductionmentioning
confidence: 99%